Identification of DNA-Microsatellite Markers for the Characterization of Somatic Embryos in Quercus suber - Gómez-Garay, Arancha; Bueno, Ángeles; Pintos, Beatriz (Microsatellites SE - 8, 2013)
Nuclear DNA-microsatellite markers led the possibility to characterize individually both Quercus suber trees and somatic embryos. The genotype inferred by SSR markers opens the possibility to obtain a fingerprint for clonal lines identification. Furthermore, allow to infer the origin of somatic embryos from haploid cells (microspores) or from diploid tissues. Using few SSR markers from other Quercus species and an automatic system based in fluorescence, it is possible to obtain a high discrimination power between genotypes. This method is sufficient to assign tissues to an individual tree with high statistical certainty. Nevertheless, it is necessary to take care to select the adequate DNA extraction method to avoid PCR inhibitors present in diverse Q. suber tissues.
The following values have no corresponding Zotero field: periodical: Microsatellites SE - 8 electronic-resource-num: 10.1007/978-1-62703-389-3_8
Keywords: Clonal lines; Doubled haploid; Dyes; Fingerprint; Germplasm; Haploid